2022
DOI: 10.4254/wjh.v14.i8.1652
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic-associated fatty liver disease is associated with low muscle mass and strength in patients with chronic hepatitis B

Abstract: BACKGROUND Although the prognostic relevance of sarcopenia has been increasingly recognised in the context of liver disease, there is a paucity of data evaluating body composition in patients with chronic hepatitis B (CHB). Beyond virus-related factors, nutritional and metabolic aspects can be associated with skeletal muscle abnormalities in these patients and should not be disregarded. AIM To evaluate the association between components of sarcopenia and demographic, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…IR and body fat mass are significantly interrelated in MAFLD patients [45]. A close correlation between MAFLD and low skeletal muscle mass has also been reported in patients with hepatitis B [46].…”
Section: Boby Composition In Fatty Livermentioning
confidence: 61%
“…IR and body fat mass are significantly interrelated in MAFLD patients [45]. A close correlation between MAFLD and low skeletal muscle mass has also been reported in patients with hepatitis B [46].…”
Section: Boby Composition In Fatty Livermentioning
confidence: 61%
“…Few studies have evaluated the association between muscle strength and NAFLD. The single-institution cross-sectional study by Santos et al [ 7 ] found that a low HGS was associated with metabolic-associated fatty liver disease in patients with chronic hepatitis B. However, because many metabolic risk factors are correlated with muscle strength and NAFLD, it was difficult to properly exclude them.…”
Section: Introductionmentioning
confidence: 99%
“…Although the body of evidence is evolving, it is worth noting that only a few cross-sectional studies have shown that sarcopenia, measured using dual-energy X-ray absorptiometry and mid-upper arm circumference, was associated with liver fibrosis in patients with MAFLD[ 15 , 16 ]. Limited evidence exists on the association between muscle strength and the prevalence of MAFLD and liver fibrosis in MAFLD in the general population[ 17 ]. In light of the public health burden of MAFLD in Asia, we investigated the association between muscle strength and MAFLD using a Korean nationally representative database.…”
Section: Introductionmentioning
confidence: 99%